2017
DOI: 10.1111/ejn.13587
|View full text |Cite
|
Sign up to set email alerts
|

Finger pressure adjustments to various object configurations during precision grip in humans and monkeys

Abstract: In this study, we recorded the pressure exerted onto an object by the index finger and the thumb of the preferred hand of 18 human subjects and either hand of two macaque monkeys during a precision grasping task. The to-be-grasped object was a custom-made device composed by two plates which could be variably oriented by a motorized system while keeping constant the size and thus grip dimension. The to-be-grasped plates were covered by an array of capacitive sensors to measure specific features of finger adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…This relationship could be explained by microvascular brain pathology that is associated with motor impairment [29]. Humans adjust finger pressure to precisely grip various visual objects, and this action involves many processes including those related to perception and cognition [28,30]. Furthermore, it was reported that manual dexterity declines in MCI patients [11] and that muscle strength is associated with the incidence of Alzheimer's disease and MCI [31].…”
Section: Discussionmentioning
confidence: 99%
“…This relationship could be explained by microvascular brain pathology that is associated with motor impairment [29]. Humans adjust finger pressure to precisely grip various visual objects, and this action involves many processes including those related to perception and cognition [28,30]. Furthermore, it was reported that manual dexterity declines in MCI patients [11] and that muscle strength is associated with the incidence of Alzheimer's disease and MCI [31].…”
Section: Discussionmentioning
confidence: 99%
“…During mECoG recording, an optical 3D motion analyzer (Qualisys Motion Capture System; Qualisys North America Inc, Charlotte, USA), in which the X-, Y-and Z-axes corresponded to the anterior, lateral and dorsal directions, respectively, was used to record the spatial position over-time a of adhesive infrared-reflective spherical markers (weight: 0.04 g, diameter: 0.30 cm) placed on the observer rat (Figures 1A and 1B), through three infrared cameras positioned around the box. This setup was previously employed to evaluate kinematics of ICMS-evoked movements in rats [19][20][21] as well as grasping in non-human primates 62,63 . To verify the absence of possible forelimb movements, one marker was positioned on the forelimb skin, i.e., the dorsal middle of the wrist.…”
Section: Observational Taskmentioning
confidence: 99%